Using phenomenography to build an understanding of how university people conceptualise their community-engaged activities. Issue 4 (3rd July 2016) - Brown, Kim; Shephard, Kerry; Warren, David; Hesson, Gala; Fleming, Jean
ABSTRACT: Higher education institutions are seeking greater community engagement through academic, social and civic activity. In response, researcher attention has turned to impacts on students' education, and benefits to both university and community partners. This phenomenographic study examines how a diverse group of teachers, researchers and administrators at one New Zealand university conceptualised their involvement in community-engaged learning and teaching. We identified an outcome space where university people conceived their community engagement in three ways: within an expert/novice discourse, as advocacy, and in the most complex conception, as reciprocal learning. When working with and within communities, we suggest that university people should be supported to approach community engagement as reciprocal learning rather than adopting approaches that render community partners in passive roles.